How Did America Inspire Indonesian Revolution? - Susilo, I Basis; Pratamasari, Annisa (Global Strategis, 2018)
This paper examines the American Revolution as an inspiration for Indonesia's founding fathers to fight for their nation's independence in 1945. This paper was sparked by the existence of  the pamphlet ‘It's 1776 in Indonesia' published in 1948 in the United States which presupposes the link between Indonesian Revolution and the American Revolution. The basic assumption of this paper is that Indonesian founding fathers were inspired by the experiences of other nations, including the Americans who abolished the British colonization of 13 colonies in North American continent in the eigthenth century. American inspiration on the struggle for Indonesian independence was examined from the spoken dan written words of three Indonesian founding fathers: Achmad Soekarno, Mohamad Hatta and Soetan Sjahrir. This examination produced two findings. First, the two Indonesian founding fathers were inspired by the United States in different capacities. Compared to Hatta and Sjahrir, Soekarno referred and mentioned the United States more frequent. Second, compared to the inspirations from other nations, American inspiration for the three figures was not so strong. This was because the liberal democratic system and the American-chosen capitalist system were not the best alternative for Soekarno, Hatta and Sjahrir. Therefore, the massive exposition of the 1776 Revolution in 1948 was more of a tactic on the Indonesian struggle to achieve its national objectives at that time, as it considered the United States as the most decisive international post-World War II political arena.